2015
DOI: 10.1159/000430207
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salusin-ß on Peroxisome Proliferator-Activated Receptor Gamma Gene Expression in Vascular Smooth Muscle Cells and its Possible Mechanism

Abstract: Background/Aims: salusin-ß is considered to be a potential pro-atherosclerotic factor. Regulation and function of vascular smooth muscle cells (VSMCs) are important in the progression of atherosclerosis. Peroxisome proliferator-activated receptor gamma (PPARγ) exerts a vascular protective role beyond its metabolic effects. Salusin-ß has direct effects on VSMCs. The aim of the present study was to assess the effect of salusin-ß on PPARγ gene expression in primary cultured rat VSMCs. Methods: Western blotting an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Interestingly, Bacchiega et al found that the IL-6-blocking agent tocilizumab significantly reduced CRP concentrations, together with parameters of systemic inflammation [26]. IL-6 has many other functions, including activation of macrophages [27, 28] and stimulation of endothelial [29, 30] and vascular smooth muscle cells [31, 32]. Although IL-6 and miR-29b both have a number of clear effects on different stages in the formation of atherosclerosis and are, individually, important markers for CVD, we have shown that that the combination of miR-29b and IL-6 offers a better predictive marker for atherosclerosis than either miR-29b or IL-6 alone.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Bacchiega et al found that the IL-6-blocking agent tocilizumab significantly reduced CRP concentrations, together with parameters of systemic inflammation [26]. IL-6 has many other functions, including activation of macrophages [27, 28] and stimulation of endothelial [29, 30] and vascular smooth muscle cells [31, 32]. Although IL-6 and miR-29b both have a number of clear effects on different stages in the formation of atherosclerosis and are, individually, important markers for CVD, we have shown that that the combination of miR-29b and IL-6 offers a better predictive marker for atherosclerosis than either miR-29b or IL-6 alone.…”
Section: Discussionmentioning
confidence: 99%
“…The primary VSMCs separated from the thoracic aorta of male Sprague Dawley (SD) rats were cultured in DMEM supplemented with 10% FBS, 100 U/ml penicillin and 100 U/ml streptomycin at 37℃ in a 5% CO 2 incubator as previously described [30, 31]. The cells showed the typical “hill and valley” morphology and 99% purity as identified by the immunofluorescence staining with α -smooth muscle-actin antibody (showed in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…To extract the total proteins, tissues were rapidly dissected and homogenized in lyses buffer [50 mM Tris–HCl, pH 7.4; 1 mM EDTA; 100 mM NaCl; 20 mM NaF; 3 mM Na 3 VO 4 ; 1 mM PMSF with 1% (v . v ‐1 ) Nonidet P‐40; and protease inhibitor cocktail], and then kept on ice for 30 min (Meng et al, ; Xu et al, ; Yao et al, ). The lysates were centrifuged at 12 000 × g for 15 min, and the supernatants were harvested.…”
Section: Methodsmentioning
confidence: 99%